Comparative Efficacy of Clinic-Based and Telerehabilitation Application of McKenzie Therapy in Chronic Low-Back Pain - Mbada, chidozie emmanuel; dada, olarewaju; ayanniyi, olusola; johnson, olubusola (International Journal of Telerehabilitation, 2023)
Vol. 11, No. 1 p.18 pub.International Journal of Telerehabilitation doi:(10.5195/ijt.2019.6260)